RISK MANAGEMENT MECHANISMS IN INNOVATION FINANCING - Alikulov Khazrat Amirkulovich (Journals Park Publishing, 2025)
This article analyzes modern financial mechanisms for financing startup projects, including incubators, accelerators, and crowdfunding platforms. During the study, the practical experience of such large international initiatives as Y Combinator, Techstars, 500 Global, Kickstarter, Indiegogo, Wefunder was studied. These mechanisms will reveal their role in supporting young entrepreneurship and innovative ideas, expanding opportunities for attracting investments, and ensuring the sustainable development of the startup ecosystem. Also, the prospects for the implementation of these mechanisms in the conditions of Uzbekistan and proposals for the development of a national startup environment have been developed.
Keywords: Startup, small business, incubator, accelerator, crowdfunding, venture capital, investment, innovative projects, financial mechanisms, young entrepreneurship, global experience.